2022
DOI: 10.1002/celc.202200092
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Performance Relationship of LaFe1‐xCoxO3Electrocatalysts for Oxygen Evolution, Isopropanol Oxidation, and Glycerol Oxidation

Abstract: Mitigating high energy costs related to sustainable H2 production via water electrolysis is important to make this process commercially viable. Possible approaches are the investigation of low‐cost, highly active oxygen evolution reaction (OER) catalysts and the exploration of alternative anode reactions, such as the electrocatalytic isopropanol oxidation reaction (iPOR) or the glycerol oxidation reaction (GOR), offering the possibility of simultaneously lowering the anodic overpotential and generating value‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…The literature about the electrooxidation of alcohols and polyols (different from methanol) on perovskite oxides is scarce, except for those related to SOFC, which are out of the scope of this review. Apart from the study performed by some of us using glycerol, there is one preliminary research about the electrooxidation of ethanol on LaRuO3 and SrRuO3 184 and another about the electrooxidation of glycerol and isopropanol on LaFe1-xCoxO3 performed by Dulce Morales et al 199 . Santiago et al 200 studied the electrochemical oxidation of glycerol on LaNiO3 and LaCoO3 and identified the reaction pathway involving the formation of glycolic acid, oxalic acid and formic acid.…”
Section: (Electro-)oxidation Of Alcohols and Polyols On Metal Oxidesmentioning
confidence: 99%
“…The literature about the electrooxidation of alcohols and polyols (different from methanol) on perovskite oxides is scarce, except for those related to SOFC, which are out of the scope of this review. Apart from the study performed by some of us using glycerol, there is one preliminary research about the electrooxidation of ethanol on LaRuO3 and SrRuO3 184 and another about the electrooxidation of glycerol and isopropanol on LaFe1-xCoxO3 performed by Dulce Morales et al 199 . Santiago et al 200 studied the electrochemical oxidation of glycerol on LaNiO3 and LaCoO3 and identified the reaction pathway involving the formation of glycolic acid, oxalic acid and formic acid.…”
Section: (Electro-)oxidation Of Alcohols and Polyols On Metal Oxidesmentioning
confidence: 99%
“…A series of LaFe 1‐ x Co x O 3 perovskite materials were developed for electrocatalytic OER, isopropanol oxidation reaction (iPOR) and glycerol oxidation reaction (GOR). [ 65 ] A structure/metal composition–activity relationship was investigated and different trends were observed for different oxidation reactions, which was derived from different active sites and reaction intermediates involved. By contrast, the electrochemical surface areas were proved to have no correlation with the electrochemical oxidation reaction activities.…”
Section: Design Of Anodic Electrocatalysts For Hybrid Water Electrolysismentioning
confidence: 99%
“…The literature about the electrooxidation of alcohols and polyols (different from methanol) on perovskite oxides is scarce, except for those related to SOFC, which are out of the scope of this review. Apart from the study performed by some of us using glycerol, there is one preliminary research about the electrooxidation of ethanol on LaRuO3 and SrRuO3 184 and another about the electrooxidation of glycerol and isopropanol on LaFe1-xCoxO3 performed by Dulce Morales et al 199 . Santiago et al 200 Based on the fundamental knowledge about the electrooxidation of methanol on metal oxides, of polyols on metals, and the several products detected in the oxidation of alcohols with several carbons, we hypothesized several adsorption intermediates for the electrooxidation of polyols on metal oxides (Figure 16).…”
Section: (Electro)oxidation Of Alcohols and Polyols On Metal Oxidesmentioning
confidence: 99%